PEMANFAATAN TEKNOLOGI DIGITAL DALAM MENINGKATKAN EFEKTIFITAS PROSES PEMBELAJARAN SEKOLAH DASAR - Rahayu, Rusnai; Rambe, Nadya; Namira, Ikrima; Nasution, Apriyani (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2026)
The utilization of digital technology has become a crucial strategy for enhancing the effectiveness of learning processes in elementary schools in response to the demands of 21st-century education. This article aims to comprehensively analyze the role of digital technology in improving students’ learning motivation, engagement, and understanding, as well as to identify its benefits, challenges, and implementation strategies in elementary education. The research employed a literature review method by examining relevant national and international journal articles, books, and educational policy reports published between 2018 and 2025. The findings indicate that the integration of digital technologies—such as interactive media, online learning platforms, learning management systems (LMS), simulations, and educational applications effectively enhances learning effectiveness through more visual, flexible, and student-centered instructional approaches. Furthermore, digital technology supports adaptive and collaborative learning while strengthening students’ 21st-century skills. However, its implementation still faces challenges, including limited infrastructure, insufficient teachers’ digital literacy, and inadequate parental support. Therefore, integrated strategies involving teacher capacity building, infrastructure development, and multi-stakeholder collaboration are essential to ensure the optimal and sustainable use of digital technology in elementary school learning. ABSTRAK Pemanfaatan teknologi digital menjadi salah satu strategi penting dalam meningkatkan efektivitas proses pembelajaran di Sekolah Dasar seiring dengan tuntutan pendidikan abad ke-21. Artikel ini bertujuan untuk menganalisis secara komprehensif peran teknologi digital dalam meningkatkan motivasi, keterlibatan, dan pemahaman belajar siswa sekolah dasar, serta mengidentifikasi manfaat, tantangan, dan strategi implementasinya. Metode penelitian yang digunakan adalah studi literatur dengan menelaah artikel jurnal nasional dan internasional, buku, serta laporan kebijakan pendidikan yang relevan pada rentang tahun 2018–2025. Hasil kajian menunjukkan bahwa integrasi teknologi digital seperti media interaktif, platform pembelajaran daring, Learning Management System (LMS), simulasi, dan aplikasi edukatif terbukti mampu meningkatkan efektivitas pembelajaran melalui penyajian materi yang lebih visual, fleksibel, dan berpusat pada siswa. Selain itu, teknologi digital mendukung pembelajaran adaptif, kolaboratif, dan penguatan kompetensi abad ke-21. Namun, implementasi teknologi masih menghadapi kendala berupa keterbatasan infrastruktur, literasi digital guru, serta dukungan orang tua. Oleh karena itu, diperlukan strategi integratif melalui peningkatan kompetensi guru, penguatan infrastruktur, dan kolaborasi berbagai pihak agar pemanfaatan teknologi digital di sekolah dasar dapat berjalan optimal dan berkelanjutan.